Continuity of Local Identity in The Multicultural Neighborhood - Jaya, R Clarrio Dimassetya; Pradoto, Wisnu (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
A century ago, Sosrowijayan Wetan was a homogenous place and all of its inhabitants were Javanese. However, tourist accommodation development in the area gave rise to globalization. As a result, Sosrowijayan Wetan transformed into an international tourist neighborhood, especially for backpackers. The differences of value between expatriates and local people stimulated transformation in Sosrowijayan Wetan, for instance, in spatial and socio-cultural aspects. The destabilizing effect of this transformation involved a highly complex process with an important consequence in the continuity of the local identity. The purpose of this study was to investigate the continuity of local identity in Sosrowijayan Wetan. A constructivist grounded theory as qualitative methods was utilized. The transcribed data were constantly built into a collective story. It was found that most insiders continued to hold onto and identify with the traditional ways of life and felt strong ties to their neighborhood. However, the structures and the values in this community seemed to be more resistant to change. Therefore, local initiative for cultural resilience became more important because the decline of local culture might lead to more multicultural problems. For instance, if the insiders were not interested in supporting the initiative through their participation in the organization, multicultural interaction problems would proliferate. This relationship influenced the continuity of local identity through its adaptation strategy for the cultural resilience.